Climatology of upper air temperature in the Eastern Mediterranean region - Philandras, C. M.; Nastos, P. T.; Kapsomenakis, I. N.; Repapis, C. C. (Atmospheric Research, 2015)
The goal of this study is to contribute to the climatology of upper air temperature in the Mediterranean region, during the period 1965-2011. For this purpose, both radiosonde recordings and gridded reanalysis datasets of upper air temperature from National Center for Environmental Prediction-National Center for Atmospheric Research (NCEP-NCAR) were used for seven barometric levels at 850. hPa, 700. hPa, 500. hPa, 300. hPa, 200. hPa, 150. hPa and 100. hPa. Trends and variability of upper air temperature were analyzed on annual and seasonal basis. Further, the impact of atmospheric circulation, by means of correlation between upper air temperature at different barometric levels and specific climatic indices such as Mediterranean Oscillation Index (MOI), North Sea Caspian Pattern Index (NCPI) and North Atlantic Oscillation Index (NAOI), was also quantified. Our findings have given evidence that air temperature is increasing at a higher rate in lower/middle troposphere against upper, and this is very likely due to increasing greenhouse gas concentrations. © 2013 Elsevier B.V.
Keywords: air temperature; annual variation; Atlantic Ocean; atmospheric circulation; Caspian Sea; climate prediction; Climatology; Eastern Mediterranean; Mediterranean Region; MOI; NAOI; NCEP-NCAR reanalysis; NCPI; North Atlantic Oscillation; North Sea; radiosonde; Reanalysis; regional climate; seasonal variation; troposphere; Upper air temperature; Upper-air temperature